Através do espelho: o reconhecimento das mulheridades transgêneras - Cruz Neto, Manoel Pereira da (2018)
“Through the mirror: the recognition of transgender womanhood” presents the results of my immersions in the world of sexuality, especially in the experiences of women from Goiania who resist power devices that normalize, categorize and inscribe on sexuality through transgender adjectivization. From a dialogical listening with hermeneutical ground along with life-stories of women who experience transgenderhood, it was aimed to listen and comprehend the processes of self and the social recognition performed in their womanhood expressions. Reflections over conceptual categories that normalize and inscribe on bodies and human sexuality cover the main basis of this dissertation writing. We discuss, such as the clinical listening, the relations established between the language that constructs subjectivity and their life-stories that reveal acknowledgments and nominations of such women, who, despite symbolic, discursive, political and social violence, do reinvent their own bodies. Also, they make it their greatest instrument and discourse in the struggle for recognition claims. Sexuality, body, transgenderhood, recognition and womanhood made up conceptual lenses that allow a glance through the mirror, from which the experiences along with subjectivities were presented. Results have shown that sexuality is a field widely used for the linguistic inscription of normativeness on the bodies, desires, affections, feelings and behaviors; transgenderhood comprise a multiplicity of non-normative expressions of sexuality; then transgenderhood is a condition imposed on these women by institutions that regulate human sexuality; the processes of recognition are plural, being the desire locus, whether sexual or the affirmation of an authenticity of being a woman; and the body is constituted as a locus of power struggle and the construction of identities.